PENDEKATAN PSIKOLOGI DAN KOMUNIKASI AUDIT DALAM MENDUKUNG PENUGASAN PROFESIONAL AUDIT (Fokus Ekonomi, 2008)
In order to increase their professionalism, auditor demanded to maintain and achieved the goal ofaudit. The purpose of audit is to give opinion about auditee assertion. To achieve that purpose,there are many factors to be concerned by the auditor, which influence their task. Thepsychological and communicational factor is highly influence the auditor as they faced the auditeedirectly or non directly. The psychological skill help the auditor to self identify, maintainbehavior, keeping the self performance and self control as they communicate with the auditee. Thepsychological skill would also help the auditor to better knowing the psychological circumstancesof their client thus the atmosphere of comfort would established on auditing process. This comfortestablished by auditor, could become the entry point of auditee’s open minded nature on thefinding of facts by the auditor. Second, the communication is very important as the initial step forthe auditor to communicate the task and trusteeship of the auditee. Communication skills increasethe smoothness of audit process in order to find and analyze any necessary proves of audit.Key word: audit, auditor, auditee, opinion, assertion, psychology, communication.